A GPR-Based Test Study on the Influencing Factors of the Dielectric Constant of Cement-Stabilized Macadam Bases. (24th February 2022) - Han, Xue; Cao, Shifei; He, Hanhui
Abstract : Dielectric constant is an important parameter for the nondestructive test of cement stabilized macadam base (CSMB) on road by ground-penetrating radar (GPR). However, few studies have been reported on the quantitative relationship between the dielectric constant and the compaction degree, strength indicators, and influencing factors of CSMB. To address the problem, groups of CSMB specimens, which were different in gradation of aggregate (fine or coarse), compaction degree, and curing time, were made and tested for dielectric constant and influencing factors with the help of the Swedish MALA GPR. The relationship between the dielectric constant of CSMB and the influencing factors such as the compaction degree, moisture content, percent residues of aggregate on the sieve of maximum particle size and curing age, and the relationship between the dielectric constant and the unconfined compressive strength were investigated based on several test data and theoretical analysis. The major findings are as follows. There is a good logarithmic correlation between the dielectric constant and the compaction degree of CSMB, and quantitative functions have been established. There is a good linear relationship between the dielectric constant and the unconfined compressive strength of CSMB, and quantitative functions have been established. A comprehensive equation between the dielectric constant of CSMB and the influencing factors such as the compaction degree, moisture content, percent residues of aggregate on the sieve of maximum particle size, and curing age has been established and validated with high significance and small error. The findings are a theoretical basis for the application of GPR to the test and quality assessment of CSMB on roads.